NEUROENDOCRINE TUMORS OF THE CERVIX - K. V. Safronova; A. S. Artemieva; A. O. Nuganen; G. F. Kutusheva; D. A. Chuglova; N. A. Mikaya; I. V. Berlev; A. F. Urmancheeva; A. M. Belyaev; E. A. Ulrich (Сибирский онкологический журнал)
The purpose of the study was to summarize the available data on etiology, diagnosis, clinical symptoms and signs as well as on various approaches to the treatment of neuroendocrine cervical tumors.Material and Methods. The relevant sources were searched in the PubMed and cochrane Library systems, and publications from 1980 to 2019 were analyzed, 53 of which were used to write this review. We also included 6 case reports from N.N. Petrov National Research Center of Oncology.Results. Neuroendocrine tumors (NETs) are extremely rare and aggressive malignancies of the female genital tract, among which NETs of the cervix are the most common. Due to the rarity of these tumors, there are currently no treatment standards based on prospective, well-planned clinical trials. For these reasons, NETs present a significant therapeutic challenge for clinicians. Case reports. Six patients ranged in age from 32 to 71 years, with a median age of 46 years, were diagnosed with large-cell neuroendocrine carcinoma (4 patients) and small-cell neuroendocrine carcinoma (2 patients). One patient with stage IIIA dropped out of the follow-up schedule. Out of 5 followed up patients, 2 patients with stage IIIA and IIB died of disease progression after 6 and 11 months, respectively. One patient with stage IB1 is in remission for 16 months. Two patients with stage IIB continue to receive primary treatment.Conclusion. Neuroendocrine carcinoma of the cervix is a rare variant of cervical cancer. The choice of treatment options is decided only by a multidisciplinary team of doctors, and further research is required.